The Use of Augmented Reality-Based Learning Media: Arloopa for English Descriptive Text in Secondary School - Rohman, Abu Na'im; Mustofa, Mutmainnah; Heriyawati, Dwi Fita (Universitas Muhammadiyah Yogyakarta, 2000)
This study aims to understand the English learning process using Arloopa as a digital medium. This study uses a descriptive qualitative design. To answer the problem of the study, the researcher observed the learning and teaching process in an Islamic secondary school in Malang. Two classes were observed by immersion in the classroom to get data. To verify the data obtained, the researcher checked the learning module document. The researcher revealed that using Arloopa as a digital learning media requires additional skill technology for the teacher if the students need to be equipped with a mobile phone, which Arloopa is only working with a mobile phone. The teacher should connect the mobile phone’s display to the LCD projector so that the students can view an object displayed by Arloopa. It would be different if each student in the class utilized an Android phone.